Advances in Sustainable Catalysis: A Computational Perspective - Quesne, Matthew G.; Silveri, Fabrizio; de Leeuw, Nora H.; Catlow, C. Richard A. (Frontiers in Chemistry, 2019)
The enormous challenge of moving our societies to a more sustainable future offers many exciting opportunities for computational chemists. The first principles approach to “catalysis by design” will enable new and much greener chemical routes to produce vital fuels and fine chemicals. This prospective outlines a wide variety of different case studies to underscore how the use of theoretical techniques, from QM/MM to unrestricted DFT and periodic boundary condition, can be applied to both homogenous and heterogenous catalysts of all sizes to provide invaluable insights into the reaction mechanisms they catalyze.